Effectiveness of Maternity Infrared Electric Massage Mattress (Kapein) on Labor Pain and Progress in Primigravida during the Active Phase of Labor - Pramukani, Irka; Rowawi, Roni; S Sastramihardja, Herri; Herawati, Yanti; Nurlatifah HR, Teni; Wijayanegara, Hidayat (Genius Journal, 2024)
Introduction: Labor pain in mothers is partly caused by a reduced oxygen supply to the uterine muscles during contractions. Non-pharmacological interventions, such as electric massage with infrared therapy on the spine, can help increase oxytocin levels, which may accelerate labor progress. Objective: This study aimed to determine the effectiveness of the infrared electric massage mattress (Kapein) in reducing labor pain and enhancing labor progress in primigravida mothers during the active phase of labor. Method: A true experimental research design with a pretest-posttest control group was used. The study involved all primigravida mothers in the active phase of labor at the Musytasyfah Karawang Clinic. A total sampling technique was employed, with 30 participants divided into an intervention group (15) and a control group (15). The data were analyzed using the McNemar test. The research was conducted from April to July 2024. Results: The study found that the infrared electric massage mattress (Kapein) was effective in reducing labor pain in primigravida mothers during the active phase (p=0.000). It also demonstrated effectiveness in improving labor progress (p=0.027). Conclusion: The infrared electric massage mattress (Kapein) is effective in reducing labor pain and improving labor progress in primigravida mothers during the active phase of labor. It is suggested that this intervention be considered as an alternative tool in obstetric services and recommended for use by the Health Office in childbirth care.